Yuridis Konsolidasi Tanah Pedesaan Atas Tanah Ulayat Masyarakat Hukum Adat - Hutagalung, Bangun Nauli; Idham, Idham (Universitas Medan Area, 2021)
The objective of land consolidation is to achieve optimal land use through increased efficiency and productivity in land use so that it can fulfill the need for an orderly, healthy and orderly residential environment. Give the land owner the opportunity to enjoy the benefits of land consolidation directly. Both land price increases and other pleasures, due to the creation of an orderly environment. Improve the mapping of the results of settlement development so that land owners can enjoy it directly. Avoiding conficts that often arise in conventional land provision. Accelerate the pace of development. Land consolidation village was also found to have misuse of authority from the land consolidation committee at that time. As for the solution to the implementation of land consolidation village for the errors that occurred due to the failure to carry out the land consolidation. The process of resolving the failure that occurred with the land consolidation was the existence of a legal process through the district court, to ensure proof of ownership of the ulayat land which was the object of the land consolidation. If the legal process has been completed, the data may be re-entered for the implementation process.